Redox-Responsive Manganese Dioxide Nanoparticles for Enhanced MR Imaging and Radiotherapy of Lung Cancer - Cho, Mi Hyeon; Choi, Eun-Seok; Kim, Sehee; Goh, Sung-Ho; Choi, Yongdoo (Frontiers in Chemistry, 2017)
In this study, we synthesized manganese dioxide nanoparticles (MnO2 NPs) stabilized with biocompatible polymers (polyvinylpyrrolidone and polyacrylic acid) and analyzed their effect on non-small cell lung cancer (NSCLC) cells with or without gefitinib resistance in vitro. MnO2 NPs showed glutathione (GSH)-responsive dissolution and subsequent enhancement in magnetic resonance (MR) imaging. Of note, treatment with MnO2 NPs induced significant cytotoxic effects on NSCLC cells, and additional dose-dependent therapeutic effects were obtained upon X-ray irradiation. Normal cells treated with MnO2 NPs were viable at the tested concentrations. In addition, increased therapeutic efficacy could be achieved when the cells were treated with MnO2 NPs in hypoxic conditions. Therefore, we conclude that the use of MnO2 NPs in MR imaging and combination radiotherapy may be an efficient strategy for the imaging and therapy of NSCLC.